GAMBARAN MAKROSKOPIK DAN MIKROSKOPIK LIMPA PADA HEWAN COBA POSTMORTEM - Goni, Lidya R.; Wongkar, Djon; Wangko, Sunny (eBiomedik, 2017)
Abstract: Morphologic changes of dead cells of an organ may be used as one of the alternatives to determine the time of death. Studies about macroscopic and microscopic postmortem changes in organs related to estimation of time of death are still limited. This study was aimed to obtain the macroscopic and microscopic changes of spleen based on the variation of time intervals up to 48 hours postmortem. This was a descriptive observational study that used two domestic pigs as animal model. The results showed that the macroscopic changes in the spleen occurred at 5 hours postmortem, characterized by changes in color and length. The spleen looked darker and became shorter (15 cm to 14.5 cm). At 30 hours postmortem, whitish spots appeared on the surface of the spleen. The earliest microscopic changes occured at 5 hours postmortem, characterized by congestion of Malpighian corpuscles. At 24 hours postmortem, a lot of cells in the Malpighian corpuscles showed pyknotic nuclei, and at 48 hours postmortem, most of the cells in the Malpighian corpuscles had undergone karyorrhexis and karyolisis. Conclusion: The earliest macroscopic changes occured at 5 hours postmortem meanwhile the earliest microscopic changes occured at 5 hours postmortem as congestion of Mapighian corpuscles. The lymphocytes inside the corpuscles showed pyknotic nuclei at 24 hours postmortem and became karyorrhexis as well as karyolysis at 48 hours postmortem.Keywords: macroscopic and microscopic description, spleen, postmortem Abstrak: Perubahan morfologi sel mati dari suatu organ dapat digunakan sebagai salah satu alternatif untuk menentukan lama waktu kematian. Penelitian mengenai perubahan makroskopik dan mikroskopik postmortem dari organ-organ sebagai alternatif perkiraan waktu kematian belum banyak dilakukan. Penelitian ini bertujuan untuk mendapatkan gambaran makroskopik dan mikroskopik limpa postmortem berdasarkan variasi waktu sampai 48 jam. Jenis penelitian ialah deskriptif observasional menggunakan dua ekor babi domestik sebagai hewan coba. Hasil penelitian menunjukkan perubahan makroskopik limpa pada hewan coba mulai tampak pada 5 jam postmortem ditandai dengan perubahan warna dan panjang limpa. Limpa tampak lebih gelap dan menjadi lebih pendek (15 cm menjadi 14,5 cm). Pada 42 jam postmortem muncul bercak-bercak pucat pada permukaan limpa. Perubahan mikroskopik limpa mulai tampak pada 5 jam postmortem yang ditandai dengan kongesti korpus Malpighi. Pada 24 jam postmortem sebagian besar limfosit dalam korpus memperlihatkan inti piknotik yang menjadi karioreksis dan kariolisis pada 48 jam postmortem. Kata kunci: gambaran makroskopik dan mikroskopik, limpa, postmortem